Effect of tourism on environmental pollution: Further evidence from Malaysia, Singapore and Thailand - Azam, Muhammad; Alam, Md Mahmudul; Hafeez, Muhammad Haroon (Elsevier B.V., 2018)
An increasing number of studies reveal that tourism industry makes a substantial contribution towards socioeconomic growth and development of tourism led economies.However, tourism steered economic growth and development is achieved at the cost of environmental pollution and degradation. The main objective of this study is to examine the effect of tourists’ arrivals on environmental pollution caused by Carbon Dioxide emissions in Malaysia, Thailand and Singapore over the period of 1990–2014. Some other regressors namely energy consumption and income are also used in the multivariate model.The Zivot–Andrews test is employed to determine unit-root and presence of structural break in the data. Fully Modified Ordinary Least Squares estimator is used as an analytical technique for unknown parameters estimation.The empirical results reveal that tourism has a significant positive effect on environmental pollution in Malaysia.However, an inverse relationship between tourism and environmental pollution is observed in Thailand and Singapore.Empirical findings suggest that sustainable economic growth and development should be ensured by implementing prudent public policy where host governments must strive to promote socially and environmentally responsible tourism industries in their respective countries.